Opportunities and Challenges in Cross-Country Collaboration: Insights from the Beneluxa Initiative - Zilke Claessens; Michiel Lammens; Liese Barbier; Isabelle Huys (Taylor & Francis Group, 2024)
National pricing and reimbursement agencies face growing challenges with complex health technologies, prompting European policy advancements. Beneluxa is a cross-country collaboration involving Belgium, the Netherlands, Luxemburg, Austria, and Ireland that aims to address sustainable access to medicines. In view of the soon-to-be-implemented EU HTA Regulation, insights and experiences from stakeholders with Beneluxa cross-country collaboration could provide possible transferable learnings. Therefore, this research aims to (i) identify the opportunities and challenges faced by Beneluxa, (ii) gather insights from stakeholders, namely (possible) applicants and policymakers, within and beyond Beneluxa on the initiative and broader cross-country collaboration principles, and (iii) transfer these insights into learnings and recommendations in anticipation of the full implementation of the new HTA Regulation. Fifteen semi-structured interviews were conducted with industry and European HTA/policy stakeholders. The principal challenges discussed by stakeholders encompass hesitancy from the industry toward Beneluxa assessments, which were attributed to procedural and timeline uncertainties, legislative framework ambiguity, and challenges in terms of industry's internal organization. Another challenge highlighted is the resource-intensive nature of the procedure due to diverse approaches among member states. In addition, industry stakeholders mentioned limited communication and procedural complexity. Despite challenges, both stakeholder groups recognized important opportunities for cross-country collaboration. Transferable insights for future cross-country collaboration include transparent communication, clear legislative embedding, internal industry restructuring to facilitate joint HTAs, and member state support for conducting collaborative assessments. The study underscores diverging views among stakeholders on cross-country collaboration's potential to support HTA and the market access of complex health technologies. While acknowledging benefits, there still are challenges, including industry hesitancy, emphasizing the need for transparent communication and clear guidance in the evolving EU HTA landscape.